ETIKA BISNIS BERTRANSAKSI DALAM ISLAM (PERSPEKTIF HADIS) - Fira Nurfitri; Andi Anugrah; Hukmiah Husain (CV. Adiba Aisha Amira, 2023)
This research aims to find out the hadith about business ethics. The method used in the article is library research which involves a number of activities related to data collection methods from library sources, reading, recording and analyzing research materials. The results of this study show that the hadith about business ethics that transactions above the brother's transactions should be avoided, in accordance with religious teachings and government regulations. Business ethics in the Islamic view also includes truth, justice, and keeping promises in trade as well as sharing with charity.